MODEL UTILITAS PEMILIHAN MODA ANGKUTAN LAUT KE SABANG DAN SEBALIKNYA - Mahlil Nursyah; Muhammad Isya; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Sabang Island is a prospective tourist destination for generating regional and national income. The city of In terms of the number of lodging and visitor, Sabang is very much changed every year. The number of tourists both Domestic and Foreign has steadily increased since 2011. In 2014 the number of tourists reached 299,881 visitors and in 2015 the number of tourists reached 366,195 visitors. At present, to get to Sabang the visitors must use a boat. Currently, only two boat providers are available. One boat provider is managed by the government (KMP BRR) and another one is by private companies (KM Express Bahari). Each provider has its own services characteristics offered to prospective passengers. Therefore, in this research, we want to know the factors that influence the passenger selection between KMP BRR and KM Express Bahari. The used model is in the form of mathematical transformation which is usually called as Binomial Logit Model. This model using the dependent variable (y) is the provider name and the variable (x) of 6 variables, namely: (x2) Age, (x3) Occupation, (x5) Income, (x6), Reason for Selection Mode, and (x8) Schedule Selected. The results are presented and discussed in this paper.